Plastics in soil description and surveys – practical considerations and field guide - Weber, Collin J. (Frontiers in Soil Science, 2022)
A growing evidence base has shown that plastics are widely distributed in soils and could have negative effects on soil functions. However, within international standards for soil description, plastics are handled so far as one part of human-made artefacts. With the ongoing plastic crisis, such a simple classification may no longer be sufficient to provide a satisfactory description of plastics in soils. Based on the latest research on plastics in soils, these foreign components can no longer be understood as relevant only for soils in urban, industrial, traffic, mining and military areas. This perspective therefore aims to suggest a possible approach towards a future and more comprehensive description of plastics in soil characterization. Based on the existing definitions within the international soil description standards, a description concept and a corresponding field guide are proposed. The proposed approach comprises a recent definition of plastics and guidelines for the description of visible plastic residues in soils during field work. Classification approaches are developed for plastics abundance and distribution as well as plastic characteristics. Furthermore, pitfalls during the description, as well as during the extraction of plastics from soils in the field, and further limitations are discussed. Basic soil description during soil surveys or soil mapping, are a strong tool of soil science to derive environmental data sets. The perspective and the field guide presented in this paper are intended to change this circumstance and enable soil scientists to describe plastic residues in soils simple, comparable and adapted to existing standards in future.